Molecular diversity of pseudomonas fluroescens antagonistic to ralstonia solanacearum - Sindhu C Cheeran (Centre for Plant Biotechnology and Molecular Biology, College of Horticulture, 2008)
The study on “Molecular diversity of Pseudomonas fluorescens antagonistic to Ralstonia solanacearum” was conducted at the Centre for Plant Biotechnology and Molecular Biology, College of Horticulture, Vellanikkara, during the period from August 2006 to May 2008. Pseudomonas fluorescens is an efficient bacterial antagonist effective against various soil-borne plant pathogens. The present investigation was carried out to assess the diversity of P. fluorescens isolates from the Western Ghats of Kerala and their antagonistic activity against Ralstonia solanacearum. Fourteen isolates of fluorescent psuedomonads tentatively identified as Pseudomonas fluorescens were isolated from different areas coming under the Western Ghats of Kerala. The isolates were maintained in sterile water, as stabs and also as glycerol stocks. Diversity of these isolates were studied by various morphological, physiological and biochemical tests. The antagonistic activity of these isolates was tested against Ralstonia solanacearum, which causes bacterial wilt in tomato. Five potential isolates which showed good antagonism under in vitro conditions, were selected and their efficacy was tested using tomato plants under pot culture condition. One of the native isolates Pf-3 collected from Malappuram tract was found to be effective in controlling wilt incidence. Molecular diversity was analyzed using Random Amplified Polymorphic DNA (RAPD) and rep-PCR. RAPD analysis was carried out using 10 different primers. All the primers except OPN 4 showed 100 per cent polymorphism. For OPN 4, a unique monomorphic band was amplified in all the isolates. The genetic similarity matrix gave the highest value of 0.92 between pf-1 and Pf-2 isolate followed by 0.90 between Pf-1 and Pf-3. In rep-PCR genomic fingerprinting, DNA primers complementary to highly conserved repetitive DNA sequences, present in the genomes of bacteria are used for amplification. Four different rep primers were used in the present analysis. The similarity coefficient was 1.0 for Pf-1 and Pf-2 followed by 0.96 for Pf-3. High degree of diversity was observed among the isolates at molecular level as detected by RAPD and rep-PCR. Even though, the three isolates Pf-1, Pf-2 and Pf-3 (collected from Malappuram) were grouped in a single cluster in all the dendrograms, slight differences were seen in the gel profiles indicating that they were not genetically identical. The results indicate that diversity among bacterial isolates within a single species, not detected by routine tests like cultural, morphological, physiological and biochemical characterization can be assessed by using molecular tools like RAPD and rep-PCR.